Uruguay : 2015 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Uruguay. (IMF Staff Country Reports; Country Report ;, 2016)
Uruguay has achieved more than a decade of high and inclusive economic growth, supported by social stability and reduced regional linkages. The country has weathered the recent global and regional headwinds relatively well so far. Yet the economy is slowing down, while inflation remains above target, and deposit dollarization has risen. While the baseline projection foresees a temporary and moderate slowdown, the country is exposed to further shocks, especially from the immediate region.